Pengaruh Pengetahuan Pajak Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Di Kabupaten Sleman Daerah Istimewa Yogyakarta - Fensiana Moi; Zulkifli Zulkifli (IKRAITH-EKONOMIKA, 2026)
This study was conducted to analyze the effect of tax knowledge, taxpayer awareness, and tax sanctions on taxpayer compliance in Sleman. The independent variables examined in this research were tax knowledge, taxpayer awareness, and tax sanctions, while taxpayer compliance served as the dependent variable. This study employed a quantitative research approach, with data collected through questionnaires distributed to taxpayers in Sleman Regency. The study involved 127 respondents selected using a purposive sampling technique. Data were analyzed using SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. Partially, tax knowledge had a positive and significant influence on taxpayer compliance with a significance level of 0.000. Taxpayer awareness also showed a positive and significant effect on taxpayer compliance with a significance value of 0.000. Furthermore, tax sanctions were found to have a positive and significant effect on taxpayer compliance with a significance value of 0.004. Simultaneously, tax knowledge, taxpayer awareness, and tax sanctions significantly affected taxpayer compliance